Políticas públicas de educação: condições de trabalho do professor: os reflexos do uso do mimeógrafo no dia-a-dia dos professores e dos alunos da rede estadual paulista – ensino fundamental I. - Campos, Joseane Gomes (2009)
This qualitative-oriented research was carried out to study the actual work conditions of elementary school I teachers, in order to unveil the portrait of public education in the twenty-first century which is taken as the “Cyber age," where technological innovations advance at a very fast speed with a view innovations in the area of information technology and communication among others. The analysis and reflection about the questions on the issues relating to such conditions with a view to the quality of education and the progress of humanity through education are justified because of its extreme social relevance. Research Object: technology available to students and teachers of the initial series and from first to fourth series of both sexes of elementary school in a public school state of Sao Paulo city – Capital. Research Problem: the reflections caused by the use of the mimeograph (a duplicator for making many copies from a stencil) to the teachers and students of elementary school – cycle one – of the network in Sao Paulo state , as a didactic-pedagogic resource. As an educator, I have observed how the protagonists of school education - students and teachers - are directly affected by the resource mentioned above, as they are social subjects participants of a school system that generates the teaching-learning process, which is formulated by education public policies, which unfortunately, sometimes they come across with obstacles that block the applicability of the same, although they are legally proclaimed. Methodological Procedures: bibliographical research to the theme by reference, structured questionnaire, and participant observation. I think it is responsibility of the educational authorities of all education systems, specially the State System, to develop new formulations on the applicability of funds to effectively contribute to the technological advance, in order to achieve the quality of public education since the Elementary Education is preponderant factor to the impetus for the social, political and economic of social subjects, who act or will act in civil society.